Court-based volleyball video summarization focusing on rally scene - Itazuri, T.; Fukusato, T.; Yamaguchi, S.; Morishima, S. (IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2017)
In this paper, we propose a video summarization system for volleyball videos. Our system automatically detects rally scenes as self-consumable video segments and evaluates rally-rank for each rally scene to decide priority. In the priority decision, features representing the contents of the game are necessary; however such features have not been considered in most previous methods. Although several visual features such as the position of a ball and players should be used, acquisition of such features is still non-robust and unreliable in low resolution or low frame rate volleyball videos. Instead, we utilize the court transition information caused by camera operation. Experimental results demonstrate the robustness of our rally scene detection and the effectiveness of our rally-rank to reflect viewers' preferences over previous methods.